Análise da expressão do gene LSP1 no diagnóstico da hiperplasia prostática benigna e do câncer de próstata - Freitas, Karla Saba de (2006)
Several molecular markers have been studied in order to differentiate prostate cancer (PCa) and benign prostatic hyperplasia (BPH). They tried to help the traditional methods in the patient evaluation (PSA and digital rectal exam). This study analyzed the LSP1 gene expression by RT-PCR in BPH and prostate cancer patients. We tried to identify the specific pattern of each pathology related to the gene expression. Fifty patients more than forty years old were selected based on PSA levels > 4ng/ml or altered digital rectal exam. Twenty five healthy patients with less than thirty years old were selected as a control group. Blood sample analyses were performed as prostatic core biopsies. The final pathology was the gold standard for diagnosis defining three study groups: PCa, 24 patients; BPH, 26 patients and control, 25 patients. The study analysis was performed based on intervals of LSP1 RT-PCR expression, defined as ≥ 1, from 0.5 to 1 and < 0.5. A second study phase analyzed LSP1 expression in prostatic tissues from specimens of twenty three patients. The results in blood sample showed a clear difference in intervals of LSP1 expression for the study groups. The BPH patients presented the higher expression, prostate cancer patients with median expression and control group with the lower one. The relative risk of BPH in LSP1 expressions ≥ 1 is eleven times greater than prostate cancer. Although, it is not a specific marker for prostate cancer or benign hyperplasia. The LSP1 analysis represents a promising complementary purpose to PSA.